Analysis of the Adoption of INLISLite Library Information System with the UTAUT Model Approach at SMA Negeri 1 Jambi City - Hakim, Muhammad Furqan; Assegaff, Setiawan; Kurniabudi (Jurusan Sistem Informasi Fakultas Ilmu Komputer Universitas Sriwijaya, 2025)
SMA Negeri 1 Kota Jambi has been implementing the INLISLite library information system for seven years. However, there has not been a comprehensive evaluation of the level of success of this system. This study aims to measure the level of user acceptance of the INLISLite library information system and the factors that influence it, using the UTAUT (Unified Theory of Acceptance and Use of Technology) model. The variables used in the UTAUT model include performance expectancy, effort expectancy, social influence, and facilitating conditions. This study also considers the moderating effect of gender and age. Data were collected through questionnaires distributed to 285 respondents, consisting of teachers, students, and staff of SMA Negeri 1 Kota Jambi. Data analysis was carried out using SEM (Structural Equation Modeling) techniques through SmartPLS 4.0 software. The results showed that effort expectancy and facilitating conditions significantly influence the acceptance of INLISLite users. However, performance expectancy and social influence do not have a significant effect. Gender and age do not moderate the relationship between variables in the UTAUT model